The quantified athlete: Associations of wearables for high school athletes - Ng , K.; Ryba, T. (Advances in Human-Computer Interaction, 2018)
The adoption of wearable technology in competitive sports can be an advantage to performance and training. Athletes who use personalised data to quantify their performances with the possibilities of sharing with others may use wearables to reinforce the athletic identity. Despite these changes, few studies have actually examined the associations between wearables and developing athletes in their quest for professional sports. Student athletes (n = 437, age = 17y) still in high schools completed a web-based survey about their professional aspirations, athletic identity, and the association with wearables. Wearables were measured by ownership and usage of apps, fitness trackers, or sports watches. Odds ratio (OR) and 95% confidence intervals (CI) were reported.Most high school athletes had apps (64.3%) or fitness trackers (65.2%) and over half of the athletes (58%) had aspirations for professional sport. Athletic identity was positively associated with ownership and usage of apps and fitness trackers. The OR was greater for professional sport aspiration with fitness trackers owners (OR = 2.60, CI = 1.44-4.73) and users (OR = 4.04, CI = 2.09-7.81) than athletes without fitness trackers. Wearables were common among high school athletes and it was part of their athletic identity. For professional aspiring athletes, wearables have the potential to help provide data to support suitable training and competition schedules at a time when students may be overloaded with academic pressures.